Lived Experiences of Mothers with Diabetic Children from the Transfer of Caring Role - Maryam Khandan; Farokh Abazari; Batool Tirgari; Mohammad Ali Cheraghi (Shiraz University of Medical Sciences, 2018)
Background: Following the confirmed type 1 diabetes in children and their discharge from the hospital, the care responsibilities are transferred from nurses to mothers. These mothers are faced with many challenges to play this caring role. The aim of this study was to explore the experiences of the diabetic children's mothers from the transfer of caring role. Methods: In 2016, semi-structured interviews with Eleven Iranian mothers of children (aged≤14 year) with type 1 diabetes were conducted. Data were analyzed using Colizzi's phenomenological method. Results: The following themes emerged in this study: 'Facing the care management challenges,' 'care in the shadow of concern', and 'hard life in the impasse of diabetes'. Conclusion: The mothers of children with type 1 diabetes, who undertake the caring role that has been transferred to them by healthcare providers, are faced with many challenges. They feel a lot of concerns and experience a hard life. Thus, understanding the experiences of these mothers by the health professionals, to improve the quality of care, is necessary.